Survey in vandalism management in low cost housing Shah Alam / Mohd Fendy Samudin - Samudin, Mohd Fendy (Faculty of Architecture, Planning and Surveying, 2013)
There are many problem in maintenance work, among of them is vandalism that could be a major problem during maintenance work. The maintenance management team cannot estimate when the vandalism occured and defects the building .Maintenance team normally can be estimate the damage for the facilities around the building for an example, the maintenance team can estimate the duration when the fluorescent lamp will be damage. If the vandalism happen the maintenance team cannot estimate it. It could be all the lamp get damages or only one get damages, vandalism problem are unpredicted. The type of damages also different, it maybe the broken or the housing fall out.Maintenance team for the low cost flat housing could be the maintenance contractor, joint management body and join management corporation. The maintenance contractor will be hire by the developer to maintain the building during defect liability period (DLP), from expired of dilapidity period (DLP) .the joint management body (JMB) will be formed for the maintenance work. The joint management body will be change to Joint management corporation after strata title have been given to the joint management bodyand changing it to joint management corporation which is there are full responsibility for the resident to maintenance work